2017
DOI: 10.1186/s13059-017-1194-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between gut microbiota, plasma metabolites, and metabolic syndrome traits in the METSIM cohort

Abstract: BackgroundThe gut microbiome is a complex and metabolically active community that directly influences host phenotypes. In this study, we profile gut microbiota using 16S rRNA gene sequencing in 531 well-phenotyped Finnish men from the Metabolic Syndrome In Men (METSIM) study.ResultsWe investigate gut microbiota relationships with a variety of factors that have an impact on the development of metabolic and cardiovascular traits. We identify novel associations between gut microbiota and fasting serum levels of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
223
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(253 citation statements)
references
References 73 publications
15
223
4
2
Order By: Relevance
“…Gut microbiota has been recently found to be an important contributor to the increased serum BCAA and aromatic amino acid levels in obesity and its metabolic complications . In consistency with these studies, we observed significantly higher serum levels of BCAA (valine and leucine/isoleucine) and aromatic amino acids (phenylalanine and tyrosine) in obese children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Gut microbiota has been recently found to be an important contributor to the increased serum BCAA and aromatic amino acid levels in obesity and its metabolic complications . In consistency with these studies, we observed significantly higher serum levels of BCAA (valine and leucine/isoleucine) and aromatic amino acids (phenylalanine and tyrosine) in obese children.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, phenylalanine serum levels were found to have a negative and significant correlation with both B. plebeius and unclassified Christensenellaceae abundance. Although these correlations have not been previously reported, Christensenellaceae family abundance was negatively correlated with isoleucine and valine serum levels in Finnish adults .…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, individuals on a vegan diet are known to have an altered intestinal microbiota composition, which might partly explain the diminished capacity to produce TMAO and the tendency toward decreased cardiovascular risk in vegans compared with omnivores . In contrast, omnivorous metabolic syndrome patients are known to have a 2‐fold increased cardiovascular risk as well as increased TMAO production . Plasma TMAO level in metabolic syndrome patients has been found to be an independent risk factor for CVD‐associated mortality, and TMAO production and associated atherosclerotic risk were transmittable by FMT in mice .…”
mentioning
confidence: 99%
“…Egg yolks, milk, dairy products, organ and muscle meats, and seafood such as mollusks, crustaceans, and fish are major dietary sources of TMAO and its precursors, although whether circulating TMAO is affected by dietary source needs to be further evaluated . There are numerous studies regarding the association between TMAO and biomarkers or risk factors of CVD, increased insulin resistance, impaired glucose metabolism, and metabolic syndrome . Possible suggested mechanisms about the association between TMAO and cardiovascular risk factors could be increased cholesterol accumulation in macrophages and in foam cells of artery walls or increased human platelet hyper‐responsiveness and potential of thrombosis in higher TMAO concentrations.…”
Section: Discussionmentioning
confidence: 99%